Determining the integrated volatility via limit order books with multiple records. Issue 11 (2nd November 2017) - Liu, Yiqi; Liu, Qiang; Liu, Zhi; Ding, Deng
Abstract: The integrated volatility plays an important role in risk management and portfolio selection, the estimation methods regarding the quantity have been widely investigated, either under low-frequency data or high-frequency data, or a combination of both. In this paper, we propose a measure for the integrated volatility via limit order book data with possible presence of multiple records. The estimator is valid under mild conditions and it is easily implemented. The finite sample performance of the proposed estimator has been verified by simulation studies and we apply the method to some real high-frequency data-sets as well.